Vitamin B₆ Biosynthesis in Escherichia coli - Vella, Joseph George (My University, 1980)
The biosynthesis of vitamin B₆ (pyridoxal-5-phosphate) is investigated by tracer methodology in two pyridoxineless mutant strains of Escherichia coli B, WG2 and WG3. Pyridoxol from mutant WG2 and pyridoxal, which was converted to pyridoxol, from mutant WG3 were isolated from the culture fluid and cells, respectively, and degraded to determine the distribution of activity derived from several radioactively labelled compounds.
Competition experiments employing ¹⁴C-labelled samples of glycerol and glycolaldehyde indicate that two pathways leading to C-5', -5, -6 of pyridoxol can occur in E. coli. In mutant WG2, a mutant which closely resembles the wild-type strain, the major pathway utilizes glycerol and related trioses as the carbon source for the stuctural units of the pyridoxol carbon skeleton: C-1,-3 of glycerol yields C-2', -3,-4',-5' and -6; C-2 of glycerol yields C-2,-4 and -5 of the vitamin. In mutant WG3, the minor pathway utilizes glycolaldehhyde which supplies C-5 and -5' of pyridoxal and spares the incorporation of glycerol into this two-carbon unit. Glycerol is the source of the other six carbon atoms. The major pathway is blocked in mutant WG3 and the "glycolaldehyde pathway" becomes the sole source of vitamin B₆.
Competition experiments employing [2-¹⁴C]glycerol in the presence of either non-labelled pyruvate, acetate, or hydroxypyruvate in mutant WG2, demonstrate that the two-carbon unit, C-2,-2', required for pyridoxol biosynthesis, is derived from pyruvate. Incorporation of radioactivity derived from [2-¹⁴C]pyruvaldehde, [1-¹⁴C]ribose, and [1-¹⁴C]-acetate into C-2,-2' of pyridoxol can be rationalized by way of pyruvate.
The identity of the pyruvate-derived C₂ unit remains to be established. The normal end-products of pyruvate catabolism have been eliminated as precursors of the two-carbon unit, C-2,-2' of pyridoxol. On this basis, it is inferred that acylating agents associated with the thiamin-dependent multienzyme complex, pyruvate dehydrogenase, may be involved in the biosynthesis of the vitamin.
A hypothesis, consistent with the results obtained from the tracer experiments, is proposed for the biosynthesis of vitamin B₆. The first steps consist of acyl transfer to dihydroxyacetone-1-phosphate followed by transamination yielding an aminosugar, 4-amino-4,5-dideoxypentulose. Condensation of the aminosugar with glyceraldehyde-3-phosphate or a closely related compound derivable also from glycolaldehyde by the minor route, followed by dehydration yields pyridoxol (Scheme 27).
Radioactive pyridoxol derived from [1-³H,2-¹⁴C]glycerol indicates the loss of one tritium atom relative to ¹⁴C during the course of biosynthesis of the vitamin.
Keywords: Chemistry; Chemistry